Influence of B4C nanoparticles on mechanical behaviour of Silicon brass nanocomposite through mechanical alloying and hot pressing. Issue 15 (15th October 2019) - Clinktan, R.; Senthil, V.; Ramkumar, K.R.; Sivasankaran, S.; Al-Mufadi, Fahad A.
Abstract: This research article has concentrated to develop a novel silicon brass of [82Cu4Si14Zn]100-x – x wt.% B4 C (x = 0, 3, 6, 9, and 12) nanocomposites which were synthesized by mechanical alloying followed by vacuum hot pressing for consolidation of powders into bulk samples. Single vial planetary ball mill was used to synthesize the nanocomposite powders in which the ball-to-powder ratio of 10:1 with the milling time of 20 h was used. The milled powders were compacted and sintered simultaneously using vacuum hot pressing equipment for 1 h at 900 °C. The structural, mechanical and tribological properties were characterized and investigated by x-ray line profile analysis (XRD), scanning electron microscopy (SEM), electron backscattered diffraction images (EBSD), energy dispersive x-ray spectroscopy (EDS), Vickers microhardness, compression test, and dry sliding wear behaviour analysis. It has been found that B4 C nanoparticles had homogeneously distributed and embedded in the nanocrystallite matrix. As a result, the fabricated nanocomposites were exhibited superior properties than the conventional alloy. Here, 12 wt% B4 C reinforced silicon brass of bulk nanocomposite was produced higher hardness and compressive strength than the unreinforcement matrix. Further, the worn morphologies were evidenced the mild wear occurred at higher reinforced nanocomposites owing to decohesion and lower wear rate with considerable wear resistance.